Legal implications of limited communication in the use of non-cash food aid card - Asnat Juljana Luturmas (IAIN Salatiga, 2020)
The Kindness family of Grop Mawar, in the village of Latuhalat, helps to feel the difficulty of doing so; first, banking transactions both cash and non-cash, this is largely due to; a). Lower educated elementary school, b). Married at a very young age. Second, do not want to be in contact with a domain of reporting or a legal sphere. Third, culture sends care to the other side, out of shame or insecurity. One of the efforts that can be made to make the families vulnerable to support their own banking transactions is limited communication. Communication is limited, in systemized references through the process of receiving help, with group fellowmen to individual relief recipients, and communicating the means of offense to lack of communication limited to groups and individuals. Breaking laws can occur if the consequences of executing the continuity of the program are inaccurate and inadequately carried out, it is critical that to the extent to which this limited communication is developed, whether by using limited communication, can solve problems in the field, by making up for the mastery of raw procedures of receiving aid that should be used as a handle and communication limited to both the inside and outside of the families of the beneficiaries.